Dampak Penggunaan Bahasa Gaul Terhadap Bahasa Indonesia Pada Anak Usia Dini - Sinaga, Dinda Aulina; Sihite, Erika; Sitanggang, Fitri Romasi; Febriana, Ika; Sinaga, Lisda; Lumbantoruan, Sulastri Diana; Silalahi, Wilde Dosta Cristina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The use of slang is increasingly widespread among young children due to developments in technology and social media. This language has a positive impact in improving children's communication skills and social conditions, but it also has the potential to reduce understanding of good and correct Indonesian. This research aims to analyze the impact of using slang on Indonesian in early childhood and find solutions to reduce its negative impact. The method used in this research is a qualitative descriptive method with data collection through observation and literature analysis. The research results show that the use of slang can enrich children's vocabulary, but also cause difficulties in academic situations and formal communication. Therefore, the role of parents and teachers is very important in guiding children to differentiate between formal and informal language use.